Polymorphisms in GSTM1, GSTT1 and CYP1A1 and risk of pancreatic adenocarcinoma - Liu, G (Nature Publishing Group, 2000)
A prospective study of 149 unselected incident cases of pancreatic adenocarcinoma and 146 ethnically-matched controls found no associations between GSTM1 (adjusted odds ratio (AOR) 1.14), GSTT1 (AOR: 1.19) and CYP1A1 (AOR: 1.08) polymorphisms and pancreatic cancer susceptibility. Smoking and drinking status did not affect results. These polymorphisms do not appear to be important gene modifiers in pancreatic cancer. © 2000 Cancer Research Campaign